Optical Angular Momentum - Allen, L; Barnett, Stephen M; Padgett, Miles J (CRC Press, 2016)
Spin angular momentum of photons and the associated polarization of light has been known for many years. However, it is only over the last decade or so that physically realizable laboratory light beams have been used to study the orbital angular momentum of light. In many respects, orbital and spin angular momentum behave in a similar manner, but t